PERAN KAMPUS DALAM ADVOKASI PERUBAHAN STATUS KELEMBAGAAN ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œDARI BADAN KREDIT DESA (BKD) MENJADI LEMBAGA MIKRO KEUANGANÃƒÂ¢Ã¢â€šÂ¬Ã‚Â (LKM) DI KABUPATEN BANYUWANGI SEBAGAI UPAYA ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œPEMULIHAN EKONOMIÃƒÂ¢Ã¢â€šÂ¬Ã‚Â DI MUSIM PANDEMI COVID-19 - Emi Hidayati; AthoÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ilah Aly Najamudin (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2022)
Banyuwangi Regency in an effort to recover the COVID-19 pandemic economy has village financial assets owned by the Village Credit Agency or BKD, namely as a channeling institution for capital distribution schemes for the lower middle class, even since POJK Number 10 of 2016 concerning the institutional transformation of BKD has carried out the process institutional status, because BKD is considered not a legal entity by the government which has an impact on asset ownership status. This study is intended to advocate for institutional change policies by using advocacy theory that has an impact on the institutional status of MFIs in order to assist economic recovery during the COVID-19 pandemic. This article is a type of qualitative research with the results of the advocacy work of the Institute for Research and Community Service (LPPM) of the Islamic Institute (IAI) Ibrahimiy, Genteng, Banyuwangi Regency which was carried out in 68 villages in Banyuwangi Regency, from 2016 until now. The results of campus advocacy work realized 7 things, namely; (1) the process of analyzing problems related to regulations regarding status changes; (2) the strategic process of making steps through FGDs for all former BKDs; (3) the mobilization process to decide on the establishment of MFIs through MUMDES; (4) the action process, namely the establishment of LKM that are members of 62 former BKDs, (5) the evaluation process, namely controlling savings and loans through the community mentoring process, (6) the continuity process to maintain the continuity of the savings and loan cycle of assets, and customers in the LM, (7) Mentoring LKM institutions during the COVID-19 Pandemic season, as distributors of business capital and credit restructuring for customers. This paper concludes that the establishment of a Microfinance Institution (LKM) in the form of PT. BKD Mandiri LKM as a financial service institution that has clear asset ownership, legal entity status and is supervised by the OJK and has an impact on the economic recovery season during the Covid-19 pandemic. This advocacy process requires a policy to strengthen Microfinance Institutions as an effort to provide business capital distribution schemes that support poverty alleviation.